Pengembangan Identitas Organisasi sebagai Strategi Bisnis - Prasetyo, Yan Wahid; Himam, Fathul (Faculty of Psychology, Universitas Gadjah Mada, 2013)
This research aimed to explore how an organizational identity was used as business strategy for private TV station. Qualitative approach with traditional grounded theory was used as research design. The data were collected through observation, interview and document analysis. The study found that organizational identity can be useful as business strategy to gain market positioning. This research also emphasized a model of identity development that can be used as business strategy. Keywords: business strategy, organizational identity, TV station